Word’s Predictability Can Modulate Semantic Preview Effect in High-Constraint Sentences - Xu, Liling; Liu, Sui; Wang, Suiping; Sun, Dongxia; Li, Nan (Frontiers in Psychology, 2022)
The processing of words in sentence reading is influenced by both information from sentential context (the effect of predictability) and information from previewing upcoming words (the preview effect), but how both effects interact during online reading is not clear. In the present study, we tested the interaction of predictability effect and the preview effect in predicting reading processing. In the experiment, sentence constraint was controlled by using all high-constraint sentences as materials. We manipulated both the predictability of the target word in the sentence and the semantic relationship between the preview word and the target word as predictors of the semantic preview effect. The results showed that the semantic preview effect was present only when the target word had low predictability in the sentence but was not observed when the target word had high predictability in the sentence. The results suggest that contextual information in reading can modulate the pre-activation of words, and thus influence whether the preview word has a priming effect. The results of this study provide further evidence that reading comprehension involves an interactive system of processing multiple sources of information at multiple levels.